Anti-racist Perspectives on Sustainabilities - Datta, Ranjan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The value of this volume, entitled "Anti-Racist Perspectives on Sustainabilities", which includes insights from Black, Indigenous, immigrant, and settler communities, lies in its potential to transform our approach to environmental and social challenges. These communities have long endured the adverse effects of environmental degradation and climate change, often due to historical injustices and systemic racism. We developed more comprehensive and contextually appropriate sustainability solutions by integrating our unique knowledge, experiences, and cultural values. In this reprint, by emphasizing inclusivity and representation in decision making, we ensure that policies and initiatives address these communities' diverse needs and aspirations. Moreover, dismantling systemic racism within sustainability efforts is ethically imperative and vital to foster a more equitable and resilient society. Ultimately, embracing anti-racist perspectives on sustainability paves the way for a more sustainable future that uplifts and empowers all individuals and communities, promoting social justice alongside environmental stewardship.